Sensibility of tactile discrimination between the fingers of the dominant and non-dominant hands - Olivera P Spasojević; Zoran Obradović; Slavko Grbić; Marinko Domuzin; Aleksandra Grbić (Биомедицинска истраживања, 2013)
Introduction: . Uninjured fingers of the opposite hand are often used to control the recovery of sensibility in injured fingertips. The aim of this study is to examine the sensitivity of the surface on the fingertips between the dominant and non-dominant hand using static and dynamic two-point discrimination test and determine if there are significant differences in sensibility between the fingers of the dominant and non-dominant hands. Methods: . The research was done on 50 persons (500 fingers) using two-point test for measuring tactile discrimination of fingers (two-point discrimination test - 2PD). 2PD test is the most widely used test for the control of sensory recovery after nerve injury. Dynamic and static two-point discrimination method was used. Results: . Using the static two-point discrimination test, we found out that the highest sensibility was in the index finger in both the dominant and non-dominant hand (dominant, 2.78 ± 0.78 mm, non-dominant, 2.82 ± 0.75 mm) and the lowest sensitivity of the little finger (dominant: 3.18 ± 0.88 mm, non-dominant: 3.01 ± 0.71 mm). Using the dynamic discrimination test, we found out that the most sensitivity was of the index finger (dominant, 2.44 ± 0.71 mm, non-dominant, 2.42 ± 0.52 mm) and the lowest of the little finger (dominant, 2.67 ± 0.88 mm, non-dominant, 2.66 ± 0.71 mm). Overall, using t-test at the significance level of p = 0.05, there was no significant difference in the sensitivity of the fingers in pairs between the dominant and non-dominant hand. Conclusion: . The difference in sensitivity was not statistically significant between pairs of fingers and toes of the surveyed sensibility between the dominant and non-dominant hand (p> 0.05). Therefore, in order to monitor the recovery of sensibility, the sensibility of injured fingertips can be compared with the sensibility in fingers of opposite healthy hand.
Keywords: tactile discrimination; two-point test; the sensitivity of fingers; hand dominance